Comparative Study of Dexmedetomidine and Fentanyl to Obtund the Pressure Response to Laryngoscopy and Intubation - Thapa, Ajay Singh; Yadav, Rajesh Kumar; Dhakal, Binita (Birat Journal of Health Sciences, 2019)
Introduction: Airway manipulation during endotracheal intubation is associated with hemodynamic and cardiovascular responses. Different agents have been used to obtund the pressure response. Objectives: To evaluate the place of Dexmedetomidine for routine use during induction of anesthesia to blunt pressure response to laryngoscopy and intubation. Methodology: One hundred patients of ASA I and II were randomly divided into two groups. Group A received Midazolam (0.05 mg/kg) a n d Fentanyl (2 mcg/Kg) and group B received Dexmedetomidine (0.6 mcg/kg) 10 minutes before induction of anesthesia. Both groups were induced with Propofol (1.5 mg/Kg). In all patients after induction (loss of eye lashes reflex) tracheal intubation was facilitated using Rocuronium 1mg/kg. Baseline heart rate was noted and hemodynamic response to intubation was observed 3, 6 and 9 minutes after intubation. Results: In group A, time for loss of eyelashes reflex was 17.45±2.19 seconds and in group B it was 11.33±2.64 seconds. In group A, after intubation heart rate increased by 11.22±2.37, 5.71±1.68, 2.34±1.73 in3, 6 and 9 minutes respectively. In group A, after intubation MAP increased by 6.49±1.37, 3.30±1.15, and 1.24±1.50 from baseline in 3,6, and 9 minutes respectively. In group B after intubation heart rate increased by 2.49±0.89 from baseline at third minutes, however decreased by 2.85±1.58 and 4.73±1.86 at sixth and ninth minute respectively. In group B, MAP increased from baseline by 3.44±1.06 in third minute however decreased by 2.22±1.38 and 4.24±3.40 at sixth and ninth minutes respectively. Conclusion: Both the agents were observed to obtund pressure response to laryngoscopy and intubation however Dexmedetomidine proved to be better option compared to Fentanyl.